2008
DOI: 10.1007/s11172-008-0149-x
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent luminescence of boron difluoride β-diketonates

Abstract: Size dependent luminescence properties of boron difluoride β diketonates were detected. Most compounds investigated are characterized by noticeable hypsochromic shifts of luminescence band maxima on going from bulk crystals to microcrystals. However, a decrease in the crystal size of (dibenzoylmethanato)boron difluoride with unique supramolecular structure was accompanied by a bathochromic shift of the luminescence band maximum. Size dependent luminescence proper ties of complexes examined were analyzed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Various types of asymmetric complexes and tunable emissions have been reported. [24][25][26][27][28][29][30][31][32][33][34] Emission colors can be modulated both in the solution and in solid states. In addition, a photo-responsive ketoiminate was obtained using a dithienylethene unit.…”
Section: Building Blocks For Constructing Nanostructures and Supramolmentioning
confidence: 99%
“…Various types of asymmetric complexes and tunable emissions have been reported. [24][25][26][27][28][29][30][31][32][33][34] Emission colors can be modulated both in the solution and in solid states. In addition, a photo-responsive ketoiminate was obtained using a dithienylethene unit.…”
Section: Building Blocks For Constructing Nanostructures and Supramolmentioning
confidence: 99%
“…Among the substancesi nt his family,d ibenzoylmethanatoborond ifluoride (P1 BF 2 ,S cheme 1) is an especially interesting compound from the viewpoint of probing relationshipsb etween aggregation mode and FL properties. [23][24][25][26][27][28][29][30][31][32][33][34][35] Since the report by Mirochnik and co-workers showing that P1 BF 2 FL involves emission from arrays of molecules in crystalsi nw hich intermolecularo rbital interactions occur, [30][31][32][33][34][35] many others have observed that P1 BF 2 derivatives exhibit interesting molecular aggregation-based emissionp henomena such as mechanofluorochromism, [36][37][38][39] aggregation-induced emission (AIE), [40] and room-temperature phosphorescence. [41,42] Guided by thesee arlier efforts, we carriedo ut an investigation aimed at elucidating the FL properties and crystal-packing structures of 1BF 2 derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…As was shown above, the 1 crystal fluorescence is of complex nature and is produced by several emission centers: excimers formed as a result of p-p and C-Hyp stacking and inter-dimer interactions. In [30] we investigated size-dependent luminescent properties of boron difluoride bdiketonates. The effect of the surface increases in the course of crystal size reduction: one can observe the share of self-captured excitons producing the excimer fluorescence increase, while the effect of inter-dimer decreases.…”
Section: Resultsmentioning
confidence: 99%